El denominado Cronicón de los dominicos de mallorca (s. XVI). Edición y Estudio - José Carlos Martín-Iglesias (Exemplaria Classica, 2014)
The Chronicle of the dominicans of ma? jorca is an annalistic compilation writ- ten partly in latin and partly in catalan and preserved by the manuscript Palma de mallorca, archive of the Kingdom of majorca, c-4739, xvIIth C., ff. 38r-41v. The oldest news (in Latin) dates back to 985, while the most recent (in catalan) corre- sponds to 1552. G. llabrés edited the work in 1909, but he did not faithfully reproduce the manuscript. This paper offers the first faithful edition of the original text, study its contents and provides a linguistic anal- ysis of the news in latin.